(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: ‘Kunun-zaki’ is a local drink made from slightly fermented corn or maize, with water as the medium. It is commonly taken by the people in the northern part of Nigeria. It has high nutritional benefit, even though it can also serve as a potential source of waterborne disease if not prepared under strict hygienic condition. Objective: This study was carried out to isolate Enterobacteriaceae bacteria from ‘kunun-zaki’ drinks and to determine their antibiotic susceptibility to commonly prescribed antibiotics within Kaduna metropolis of Kaduna State, Nigeria. Methods: A total of 20 samples were randomly collected from different locations (within a period of two weeks), analysed and coliform count determined. The bacterial isolates were identified using gram staining, selective media and standard biochemical tests. Antibiotics susceptibility testing was carried out using Kirby-Bauer agar diffusion method. Results: The following bacteria were isolated: Enterobacteriaceae (50%), Staphylococcus aureus (30%), Pseudomonas aeruginosa (20%). The Enterobacteriaceae bacteria isolated were: Klebsiella pneumoniae 4 (20%), Escherichia coli 4, (20%), Citrobacter freundii 1 (5%) and Proteus vulgaris 1 (5%). The antibiotic susceptibility test revealed that ciprofloxacin, gentamicin, imipenem and ofloxacin (each 100%) chloramphenicol (90%), amoxicillin-clavulanate (80%) and streptomycin (70%) were active against the isolates while the isolates were resistant to ceftazidime (100%), meropenem (80%), cefoxitin and ceftriaxone (70%). Conclusion: This study showed the presence of Enterobacteriaceae contaminants in locally consumed drink (kunun-zaki) sold within Kaduna metropolis which pose a potential public health risk including the risk of transmission of strains which can lead to the spread of antibiotic resistance in the society.